GE_GERICHTE C/9485/2013 vom 27. März 2018 - GE Cour de justice (2018)
CONTRAT D'ENTREPRISE ; NORME SIA ; DROIT DE REPRÉSENTATION ; MODIFICATION(EN GÉNÉRAL) ; COMMANDE | CO.33.al3; CO.373.al2; CO.374; CC.3.al2